2022
DOI: 10.1108/jima-07-2021-0231
|View full text |Cite
|
Sign up to set email alerts
|

Translating the impacts of social advertising on Muslim consumers buying behavior: the moderating role of brand image

Abstract: Purpose This study aims to examine the impact of social advertising (informative, entertainment, credibility, ease of use, privacy and contents) on the buying behavior of Muslim consumers toward the fashion clothing brands during the Holy Month of Ramadan along with the moderating role of brand image. Precisely, it focuses on the marketing techniques and strategies in social advertising to enhance buying behavior. Design/methodology/approach Using the convenience sampling technique, data was collected from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 101 publications
(122 reference statements)
0
14
0
3
Order By: Relevance
“…PLS-SEM validates the relationship in systematic way, deals with a complex model in a single click, and preferable in formative models (Rehman et al. , 2017; Rehman and Al-Ghazali, 2022; Rehman and Zeb, 2022). Therefore, PLS-SEM was the best option to shape the relationship among defined variables in the proposed research framework.…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…PLS-SEM validates the relationship in systematic way, deals with a complex model in a single click, and preferable in formative models (Rehman et al. , 2017; Rehman and Al-Ghazali, 2022; Rehman and Zeb, 2022). Therefore, PLS-SEM was the best option to shape the relationship among defined variables in the proposed research framework.…”
Section: Methodsmentioning
confidence: 82%
“…The PLS-SEM approach is used to test the conjectures, no normally distributed data, preferred when a study focuses on the development of theory, and in exploratory study (Bhatia and Kumar, 2022). PLS-SEM validates the relationship in systematic way, deals with a complex model in a single click, and preferable in formative models (Rehman et al, 2017;Rehman and Al-Ghazali, 2022;Rehman and Zeb, 2022). Therefore, PLS-SEM was the best option to shape the relationship among defined variables in the proposed research framework.…”
Section: Data Analysis Techniquementioning
confidence: 99%
“…This study has applied the technique of PLS-SEM to analyze the derived data and validating the proposed research model. The study applied the techniques of factors loading, composite reliability and average variance extracted (AVE) to analyze the results of measurement model (Rehman and Zeb, 2022). In the assessment of measurement model, the results revealed that the values of factors loading (>0.7), composite reliability (>0.7) and AVE (>0.5) are greater than the recommended threshold values.…”
Section: Resultsmentioning
confidence: 99%
“…Selain itu, pemasaran produk juga harus dilakukan untuk mempertahankan pangsa pasar dengan mengikuti tren pemasaran yang ada. Konten promosi penjualan media sosial (social media sales promotion content) dan konten iklan media sosial (social media advertising content) menjadi teknik promosi yang dapat mendorong konsumen untuk mencoba berlangganan dengan membagikan informasi produk melalui media sosial (Raji et al, 2019;Weng et al, 2013;Rehman et al, 2022).…”
Section: Pendahuluanunclassified
“…Konten iklan mengenai atribut produk yang mempengaruhi kesadaran dan persepsi konsumen terhadap fungsional merek melalui informasi yang disebarkan pada media sosial (Raji et al, 2019). Social advertising yang berisikan informasi dapat mempengaruhi brand image secara positif terhadap perilaku pembelian konsumen muslim terhadap merek pakaian fashion (Rehman & Zeb, 2022).…”
Section: Social Media Advertising Content Dan Functional Brand Imageunclassified